"This is Not Who I Want to be:" Experiences of Opioid-Dependent Youth Before, and During, Combined Buprenorphine and Behavioral Treatment. (1st February 2014) - Moore, Sarah K.; Guarino, Honoria; Marsch, Lisa A.
<x xml:space="preserve">Abstract</x> Novel, qualitative data were collected from youth in treatment for opioid dependence (2009–2010) regarding their experiences with opioid dependence and combined behavioral–pharmacological treatment. Urban youth participants were recruited from a larger randomized controlled trial examining the relative efficacy of two tapers of buprenorphine–naloxone, combined with behavioral treatment (ages 13–24 eligible). Twenty-two youth participated in 1- to 1.5-hour semi-structured interviews. A grounded theory approach guided the analysis. The results have the potential to inform the development of efficacious treatments for this growing, yet understudied, group of youth. Study implications and limitations are noted, and future research is prescribed. (NIDA #1R01 DA018297).